Similar integration but different stability of Alus and LINEs in the human genome - Pavlícek, A; Jabbari, K; Paces, J; Paces, V; Hejnar, J V; Bernardi, G (Gene, 2001)
Alus and LINEs (LINE1) are widespread classes of repeats that are very unevenly distributed in the human genome. The majority of GC-poor LINEs reside in the GC-poor isochores whereas GC-rich Alus are mostly present in GC-rich isochores. The discovery that LINES and Alus share similar target site duplication and a common AT-rich insertion site specificity raised the question as to why these two families of repeats show such a different distribution in the genome. This problem was investigated here by studying the isochore distributions of subfamilies of LINES and Alus characterized by different degrees of divergence from the consensus sequences, and of Alus, LINEs and pseudogenes located on chromosomes 21 and 22. Young Alus are more frequent in the GC-poor part of the genome than old Alus. This suggests that the gradual accumulation of Alus in GC-rich isochores has occurred because of their higher stability in compositionally matching chromosomal regions. Densities of Alus and LINEs increase and decrease, respectively, with increasing GC levels, except for the telomeric regions of the analyzed chromosomes. In addition to LINEs, processed pseudogenes are also more frequent in GC-poor isochores. Finally, the present results on Alu and LINE stability/exclusion predict significant losses of Alu DNA from the GC-poor isochores during evolution, a phenomenon apparently due to negative selection against sequences that differ from the isochore composition.
Keywords: Humans; lidské chromozomy, pár 21; zastoupení bazí; Chromosomes, Human, Pair 22; lidé; Long Interspersed Nucleotide Elements; Base Composition; inzerční mutageneze; elementy Alu; DNA; dlouhé rozptýlené jaderné elementy; GC Rich Sequence; lidské chromozomy, pár 22; genom lidský; Mutagenesis, Insertional; GC bohatá sekvence; Chromosomes, Human, Pair 21; Alu Elements; Genome, Human